2016
DOI: 10.1111/jvp.12290
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the residue levels of drugs in eggs, using physicochemical properties and their influence on passive diffusion processes

Abstract: Based on a physiologically based pharmacokinetic model, describing the relationship between the plasma concentration of a drug and its deposition into eggs, general transport constants into yolk and albumen were derived, for a number of compounds, using experimental data from literature. Using only generally accepted concepts in passive diffusion theory, these transport constants were used to derive and calibrate general equations, describing the transport into yolk and albumen, in terms of the physicochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…The edible component of the eggs, the albumen and yolk, is different in physiological and chemical properties. Several published PBPK models have incorporated eggs with or without albumen and yolk being two separated compartments (Hekman & Schefferlie, 2011 ; Lautz et al., 2020 ; Schefferlie & Hekman, 2016 ). It was suggested that the inclusion of both yolk and albumen compartments can aid in predictions of residue profiles depending on the physiochemical properties of the drug (Lautz et al., 2020 ; Schefferlie & Hekman, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…The edible component of the eggs, the albumen and yolk, is different in physiological and chemical properties. Several published PBPK models have incorporated eggs with or without albumen and yolk being two separated compartments (Hekman & Schefferlie, 2011 ; Lautz et al., 2020 ; Schefferlie & Hekman, 2016 ). It was suggested that the inclusion of both yolk and albumen compartments can aid in predictions of residue profiles depending on the physiochemical properties of the drug (Lautz et al., 2020 ; Schefferlie & Hekman, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…The residue profiles of administered drugs that appeared in either egg white or egg yolk were often found to be very different ( Kan and Petz, 2000 ; Furusawa, 2001 ; Goetting et al, 2011 ). Several studies have attempted to explain the critical factors that may influence the transfer of residue and model its distribution to either egg yolk or egg white compartment ( Donoghue et al, 1997 ; Donoghue, 2001 , 2005 ; Furusawa, 2001 ; Goetting et al, 2011 ; Hekman and Schefferlie, 2011 ; Schefferlie and Hekman, 2016 ).…”
Section: Transfer Of Residues Into Eggs and Distribution Between The ...mentioning
confidence: 99%
“…They concluded that physicochemical properties of a molecule alone cannot always be used to predict its pharmacokinetics. Likewise, Schefferlie and Hekman (2016) suggested that lipid solubility alone is not the only chemical factor to influence the transfer rate and distribution of residues between the egg white and yolk compartments. Even when all of the aforementioned physicochemical parameters are taken into account, it is difficult to predict the distribution of residue between the egg white and yolk after exposure since some of the factors that determine the preference of distribution of the residues between the 2 compartments are still to be characterized ( Furusawa, 2001 ; Kan, 2003 ; Donoghue, 2005 ; Schefferlie and Hekman, 2016 ).…”
Section: Transfer Of Residues Into Eggs and Distribution Between The ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Daarom worden eisen gesteld ten aanzien van tijd en residuen voor menselijke consumptie. Daarom zijn zeer weinig diergeneesmiddelen goedgekeurd voor gebruik bij leghennen, en is het aantal geneesmiddelen met een Europese maximumwaarde voor residuen ook erg klein gebleven in de laatste jaren (Schefferlie & Hekman, 2018 een patiënt was met een resistente bacterie tegen carbapenem-antibiotica die in het water van de afvoer van de douche kon groeien en zich via de lucht verspreidde als de douche aanstond (zie ook,…”
Section: Figuurunclassified